An Integrated Approach for Revisiting Basin-Scale Heavy Oil Potential of The Central Sumatera Basin - Bambang Widarsono; Herru Lastiadi Setiawan; Tri Muji Susantoro; Suliantara Suliantara; Jonathan Setyoko Hadimuljono; Desi Yensusminar; Julikah Julikah; Ongki Ari Prayoga (Testing Center for Oil and Gas LEMIGAS, 2021)
Central Sumatra Basin is one of the most prolifi c hydrocarbon basins in Indonesia and has proved itself as being the largest contributor to Indonesia’s national crude oil production. Heavy oil fi elds in the basin, such Duri fi eld as the largest one, plays a very important role in making up the basin’s whole oil production output. In general, the Central Sumatra Basin is also acknowledged for its heavy oil potential. Accordingly, a study under the auspices of the Ministry of Energy and Mineral Resources (MEMR) of the Republic of Indonesia is carried out to re-visit the potential. The study establishes and implements an integrated approach formed by a combined macro and micro analyses. In the macro analysis, a combined evaluations of regional geology, geophysics, geochemistry, remote sensing/geographic information system ( GIS), regional geothermal study, and fi eld survey/ microbiology is performed to identify geological positions of the heavy oil potential. In the micro analysis, on the other hand, qualitative and quantitative well-log analyses supported by well-test and laboratory measurement data on the identifi ed geological positions are carried out with an aim of identifying heavy oil bearing reservoirs/traps under three categories of certainty. The main result of the study is identifi cation of 51 fi elds/structures - producing and non-producing – that bears heavy oil within the three categories. Findings of the study can certainly be used as a prerequisite for more intensive and expansive studies to meet the need for a more solid conclusion regarding the heavy oil potential of the Central Sumatra Basin.